MODELING AND CONTROL MECHANISMS AND MEASURES IN MEDICALFACILITIES IN PROVIDING EFFECTIVE PATIENT CARE - Petkova, Ivelina (E-Journal VFU, 2025)
The health care system in Bulgaria in recent years has followed a relatively stable trend, expressed in the preservation of hospital treatment facilities in the country. Reforms in the sector have significantly affected the provision of hospital services in specialized medical care. The purpose of this report is to present the structure and organization of medical facilities in the country over the past five years, to emphasize the control mechanisms and measures to prevent and treat the consequences of stroke patients, and to derive guidelines and proposals for improving patient care for them.
Keywords: patient care; medical facilities; control